Legal Aspects of HIV/AIDS : a Guide for Policy and Law Reform. - Gable, Lance (World Bank e-Library., 2007)
"This is a resource for lawyers, policy makers, and other practitioners with an interest in countries' responses to HIV/AIDS. Legal Aspects of HIV/AIDS: A Guide for Policy and Law Reform covers 65 topics in a concise, accessible format, explaining how laws and regulations can either underpin or undermine public health programs and responsible personal behavior. For each topic, the Guide summarizes the key legal or policy issues, provides relevant "practice examples" (citing actual laws and regulations) and offers a list of references that may be consulted for more information."--Jacket